PENGARUH MINAT DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR SEJARAH - Titik Winarni (Herodotus: Jurnal Pendidikan IPS, 2019)
The research aims to analyze and test the truth of hypotheses regarding the influence of Learning Interest and Independence on Learning Achievement in Social Sciences. The research hypotheses tested included: 1) The Effect of Interest on Social Studies Learning Achievement. 2) The Effect of Learning Independence on Social Science Learning Achievement. 3) The Effect of Interest and Learning Independence on Social Studies Achievement. The study was conducted by survey method. The population is grade VII students of SMP Negeri in South Jakarta, with the sampling technique used is random cluster sampling. Data analysis uses multiple regression. The results of hypothesis testing obtained the following conclusions: 1) There is a significant influence of Interest and Learning Independence together on Social Learning Achievement of Social Studies students in South Jakarta Public Middle School. This was proven by the calculated F value of 80.129 and sig = 0.000 <0.05. 2) There is a significant influence of Interest in Learning towards Social Studies Learning Achievement of South Jakarta Public Middle School students. This is evidenced by the t value of 1.997 and sig = 0.049 <0.05. 3) There is a significant influence of Learning Independence on Social Studies Learning Achievement of South Jakarta Public Middle School students. This is evidenced by the t value of 2.929 and sig = 0.004 <0.05. The results of this study are useful for increasing Student Interest and Learning Independence at the SMP level.